The Effect of “Hamburger Essay” Strategy on Students’ Ability to Write an Essay: Pre-Experimental Research at Eight Grade Students’ of SMP Negeri 24 Padang - Desrianti, Elisa; Fatimah, Sitti (Universitas Negeri Padang, 2024)
The aimed of the research was to find out how the Hamburger Essay Strategy affected the essay-writing skills of SMP Negeri 24 Padang students. A pre-experimental design with a single group pre- and post-test was employed in this research. Eight classes of eighth-grade students from SMP Negeri 24 Padang made up the population. Purposive sampling was used to choose the sample. The members of the sample were VIII.A. Thirty students were present. Writing essays was the method used to gather the data. The findings of the research showed that implementing of the Hamburger essay strategy positively affected on students’ ability to do essays, with a mean of 31.80 on the pre-test and a mean of 41.77 on the post-test. They were more confident in writing based on the situation given. In conclusionthe research's conclusions and results must improve the essay writer's skills. Students' essay-writing skills are significantly improved by the Hamburger essay strategy.